The Improvement of Science Process Skill and Learning Achievement Through the Application of Guided Inquiry Strategy of Student in SMP Negeri 26 Surakarta Class VIII-B Class Year 2011/2012 - Aksari, Yuang Dinni; Widoretno, Sri; Santoso, Slamet (BIO-PEDAGOGI, 2012)
The purposes of this research is to increase students science process skills and achievement of class VIII-B SMP Negeri 26 Surakarta through the implementa-tion of Guided Inquiry learning strategy. This research is a Classroom Action Research with 4 cycles of action. Each cycle consisting of 4 phases which is planning, acting, observing, , and reflecting. Observational data obtained from the observation, and test. Technical analysis of data is technical descriptive both qualitative and quantitative. Data validation is use split half method.Result of this research show that with the implementation of Guided Inquiry strategy could increase students science process skills and achievement in Biological learning. It’s based on the result of observation and test. Average procentage for each aspect of science process skills from the result of observation first cycle are 33,19 %  (worked up 16,97%), second cycle 43,22 % (worked up 10,03%), third cycle 48,23 % (worked up 5,01%), dan last cycle 60,38 % (worked up 12,15%). Average score of knowledge dimension of cognitive achievement on the first cycle 37,10 %, second cycle 42,64%, third cycle 37,72%, and the last cycle 45,22%. Score of affective achievement on the first cycle 18,52% (worked up 2,3%), second cycle 28,06% (worked up 9,54%), third cycle 38,73%  (worked up 10,67%), and the last cycle 45,22% (worked up 6,49%). Score of psikomotor achievement on the first cycle 38,95% (worked up 22,71%), second cycle 43,71% (worked up 4,76%), third cycle 46,39% (worked up 2,68%), and the last cycle 48,9% (worked up 2,51%). According to this result, can be concluded that the implementation of Guided Inquiry learning strategy could increase students science process skills and achievement of class VIII B SMP Negeri 26 Surakarta class year 2011/ 2012.  Key Words: Guided Inquiry, Science Process Skills, Achievement